(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2020)
One of the important steps taken by the prophet of god in his construction of the new islamic state in medina is the issuance of a document establishing relations between the new muslim community itself, and between him and the human masses that coexisted in the medina , especially the jews, as it was necessary to organize a relationship between muslims and themselves, and between muslims and other people of the medina, in order to provide security and peace for all people. Key words: Legislative texts, written, human rights, muhammad the messenger of god , medina document .